Full-Range Optical Imaging of Planar Collagen Fiber Orientation Using Polarized Light Microscopy - Turčanová, Michaela; Hrtoň, Martin; Dvořák, Petr; Novák, Kamil; Hermanová, Markéta; Bednařík, Zdeněk; Polzer, Stanislav; Burša, Jiří (BioMed research international, 2021)
A novel method for semiautomated assessment of directions of collagen fibers in soft tissues using histological image analysis is presented. It is based on multiple rotated images obtained via polarized light microscopy without any additional components, i.e., with just two polarizers being either perpendicular or nonperpendicular (rotated). This arrangement breaks the limitation of 90° periodicity of polarized light intensity and evaluates the in-plane fiber orientation over the whole 180° range accurately and quickly. After having verified the method, we used histological specimens of porcine Achilles tendon and aorta to validate the proposed algorithm and to lower the number of rotated images needed for evaluation. Our algorithm is capable to analyze 5·105 pixels in one micrograph in a few seconds and is thus a powerful and cheap tool promising a broad application in detection of collagen fiber distribution in soft tissues.
Keywords: polarizační mikroskopie; Collagen; mikroskopie; extracelulární matrix; počítačové zpracování obrazu; prasata; Microscopy; Achilles Tendon; algoritmy; Swine; kolagen; Algorithms; Achillova šlacha; zvířata; Animals; Extracellular Matrix; optické zobrazování; Microscopy, Polarization; Optical Imaging; Image Processing, Computer-Assisted